IMPROVING LISTENING AND SPEAKING SKILLS BY USING ANIMATION VIDEOS AND DISCUSSION METHOD - Rizka Amalia (State Institute for Islamic Studies IAIN of Metro, 2014)
Listening and speaking are the important skills that have to be mastered by the students. By having these skills, the students can communicate with others easily. There are many strategies that can be used to teach listening and speaking skills. One of the strategies is by using animation videos. Many students of all ages still like watching animation videos for they are interesting. Animation videos can help the students more understand because they present visual context aids that assist the students comprehend and improve their learning skills. Animation videos can be integrated with discussion method. This paper aims at providing required information about the advantages of animation videos and how to use them in the teaching and learning English activity.